Severe pneumococcal community-acquired pneumonia admitted to medical Tunisian ICU - Belkhouja, Khairallah (J Infect Chemother, 2011)
Streptococcus pneumoniae is the most common cause of community-acquired pneumonia (CAP). There are no available data about this disease in Tunisian intensive care patients. The objective of this study is to describe the clinical and microbiological features of pneumococcal CAP and determine the prognostic factors. This is a retrospective cohort study of all pneumococcal CAP cases hospitalized in the medical intensive care unit (ICU) of Hospital A. Mami of Ariana (Tunisia) between January 1999 and August 2008. Included were 132 patients (mean age, 49.5 years; 82.6% males); 30 patients had received antimicrobial treatment before hospital admission. The mean of the Simplified Acute Physiology Score II was 32.9. All patients had an acute respiratory failure; 34 patients (25.8%) had pneumococcal bacteremic CAP. Among the isolated strains, 125 antimicrobial susceptibility tests were performed. The use of the new Clinical and Laboratory Standards Institute breakpoints for susceptibility when testing penicillin against S. pneumoniae showed that all isolated strains were susceptible to penicillin. The mortality rate was 25%. The need of mechanical ventilation at admission [odds ratio (OR), 3.4; 95% confidence interval (CI), 1.67–6.94; P = 0.001), Sepsis-related Organ Failure Assessment (SOFA) score at admission ≥4 (OR, 3.1; 95% CI, 1.56–6.13; P = 0.001), and serum creatinine at admission ≥102 μmol/l (OR, 1.8; 95% CI, 1.02–3.17; P = 0.043) were independent factors related to ICU mortality. In conclusion, pneumococcal CAP requiring hospitalization in the ICU is associated with high mortality. All isolated stains were susceptible to penicillin.